Influence of Employee Compensation, Job Satisfaction, and Working Environment on Employee Retention in Nepalese Commercial Banks - Pandey, Prakash; Sharma, Binita (Nepalese Journal of Business, 2025)
This study examines the influence of employee compensation, job satisfaction, and working environment on employee retention in Nepalese commercial banks. Employee retention is the dependent variable. The selected independent variables are employee compensation, job satisfaction, organizational culture, working environment, career development, and employee recognition. The primary source of data is used to assess the opinions of the respondents regarding employee compensation, job satisfaction, organizational culture, working environment, career development, employee recognition, and employee retention. The study is based on primary data of 115 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of employee compensation, job satisfaction, and working environment on employee retention in Nepalese commercial banks. The study showed that employee compensation has a positive impact on employee retention. It indicates that increase in employee compensation leads to increase in employee retention. Similarly, job satisfaction has a positive impact on employee retention. It indicates that higher the level of job satisfaction, higher would be the employee retention. Likewise, organizational culture has a positive impact on employee retention. It indicates that supportive organizational culture leads to increase in employee retention. In addition, working environment has a positive impact on employee retention. It indicates that healthy working environment leads to increase in employee retention. Further, career development has a positive impact on employee retention. It indicates that better opportunities of career development within the organization leads to increase in employee retention. In addition, employee recognition has a positive impact on employee retention. It indicates that better mechanism of employee recognition leads to increase in employee retention.